Contemporary tourist behaviour yourself and others as tourists - Bowen, David (Of Oxford Brookes Business School) (CABI, 2022)
"Providing a cross-disciplinary approach to tourism behaviour, this fully updated edition responds to new emerging themes such as the digital revolution, social media, and tourist-risk resulting from political instability and other uncertainty. With international examples throughout, this new edition reviews both theory and practical application"--